Simulation Analysis of Dual Excitations Method for Improving the Sensitivity Distribution of an Electrical Capacitance Tomography System - Senen, Muhammad Safwan; Mohamad, Elmy Johana; Mohamad Ameran, Hanis Liyana; Rahim, Ruzairi Abdul; Faizan, Omar Mohd; Mohd Muji, Siti Zarina (International Journal of Integrated Engineering, 2017)
A well-known challenge in using an Electrical Capacitance Tomography (ECT) system to obtain cross-section image of pipelines is the system’s non-uniform sensitivity distribution where the system is less sensitive at the pipe’s centre compared to the pipe’s wall proximity. A method to overcome this issue is by using two The aim of this work is to analyse the sensitivity map distribution by using two excitation potentials technique (1) to observe the changes of the inter-electrode capacitance and the permittivity of the dielectric material, (2) to investigate the distribution of electrical potential at the centre of the pipe, also (3) to investigate the feasibility of two excitation potentials technique to improve the sensitivity map in ECT system. The COMSOL Multiphysics software is used to simulate an ECT system to obtained results by generated phantoms, measured values such capacitance value and electrical potential, also for the sensitivity map distribution in the pipe model. By using this technique, an improvement is made on the sensitivity map distribution in the central area.